Effect of Laser Contrast on MeV Protons From Relativistic Laser-Solid Interactions (Bangladesh Journal of Physics, 2023)
Results on acceleration of MeV protons from 100 TW Ti:Sapphire laser system is presented in this paper. By irradiating few micrometers thick aluminum foils with 30 fs laser pulse with intensity of 1020 W cm-2, protons with energy exceedingly more than 10 MeV were detected. However, on increasing our laser contrast by 2 orders of magnitude (10-8 to 10-10), we observe a nearly 4.5 times enhancement in the proton flux, with a slight reduction in the proton cut-off energy. These results open a prospect of producing high flux of MeV-class proton beams.Bangladesh Journal of Physics, Vol. 30, Issue 2, pp. 77–80, December 2023